Relevance of intra operative bacteriology culture in primary total knee replacement - Yaakub, Yuzaimi (2016)
Prosthetic joint infection following joint replacement is uncommon but can be a devastating complication. The rate of deep infection following primary total knee replacement is less than 2%. However, it remains a challenge to be encountered despite the advances in surgery nowadays. This study was a retrospective cross sectional study. The aim of this study was to determine whether obtaining bacteriology swabs for culture and sensitivity at the time of surgery could help in further reducing the rate of infection following primary total knee replacement. A bacteriology swab of the synovial fluid was taken immediately after opening the capsule of the knee joint and was sent for culture and sensitivity. Out of 140 swabs sent, none was found to be positive. Postoperatively, 2 (1.4%) of the patients developed deep infection whereas 36 (25.7%) developed superficial infection. Intra-operative bacteriology swab in primary total knee replacement has limited role in future prediction of incidence and management of postoperative prosthetic joint infection in total knee joint replacement surgery. This study also showed that there was no association found between risk factors such as age, gender, obesity, diabetes mellitus, rheumatoid arthritis, smoking and prolong duration of surgery, with post-operative superficial and deep infection. Keywords: Bacteriology swabs; primary total knee replacement; deep infection; prosthetic joint infection